Cold-Inducible RNA-Binding Protein Prevents an Excessive Heart Rate Response to Stress by Targeting Phosphodiesterase. Issue 12 (5th June 2020) - Xie, Duanyang; Geng, Li; Xiong, Ke; Zhao, Tingting; Wang, Shuo; Xue, Jinfeng; Wang, Cheng; Wang, Guanghua; Feng, Zhiqiang; Zhou, Huixing; Li, Yini; Li, Li; et al.
Abstract : Rationale: The stress response of heart rate, which is determined by the plasticity of the sinoatrial node (SAN), is essential for cardiac function and survival in mammals. As an RNA-binding protein, CIRP (cold-inducible RNA-binding protein) can act as a stress regulator. Previously, we have documented that CIRP regulates cardiac electrophysiology at posttranscriptional level, suggesting its role in SAN plasticity, especially upon stress conditions. Objective: Our aim was to clarify the role of CIRP in SAN plasticity and heart rate regulation under stress conditions. Methods and Results: Telemetric ECG monitoring demonstrated an excessive acceleration of heart rate under isoprenaline stimulation in conscious CIRP-KO (knockout) rats. Patch-clamp analysis and confocal microscopic Ca 2+ imaging of isolated SAN cells demonstrated that isoprenaline stimulation induced a faster spontaneous firing rate in CIRP-KO SAN cells than that in WT (wild type) SAN cells. A higher concentration of cAMP—the key mediator of pacemaker activity—was detected in CIRP-KO SAN tissues than in WT SAN tissues. RNA sequencing and quantitative real-time polymerase chain reaction analyses of single cells revealed that the 4B and 4D subtypes of PDE (phosphodiesterase), which controls cAMP degradation, were significantly decreased in CIRP-KO SAN cells. A PDE4 inhibitor (rolipram) abolished the difference in beating rate resulting from CIRP deficiency. The mechanistic study showed that CIRP stabilized the mRNA of Pde4b and Pde4d by direct mRNA binding, thereby regulating the protein expression of PDE4B and PDE4D at posttranscriptional level. Conclusions: CIRP acts as an mRNA stabilizer of specific PDEs to control the cAMP concentration in SAN, maintaining the appropriate heart rate stress response. Abstract : Supplemental Digital Content is available in the text.